ANALISIS FUNGSI DISTRIBUSI KEUANGAN NEGARA (Studi Pemikiran ’Abdul Qadim Zallum) - Nunung Nurlaela (Millah: Journal of Religious Studies, 2015)
Indonesian budget deficit from year to year, and the other hand haven’t been able to improve the life of people with evenly and the economic assets aren’t placed on proper tipping point, so we need a new way. This study presents an alternative formulation of the budget options with a focus on the distribution function, use qualitative method with a phenomenological approach and using descriptive analysis. The emphasis of this study is the distribution function of the state budget that was initiated by Shaikh Abdul Qadim Zallum and their application with a case study in 2010-2012 Indonesian budget. The result is the state will be able to flatten the welfare of people at once to function, rolling the industrialization process, without deficit. Economic stability will be a real foundation for economic growth. The development program based on Islamic political economy requires bureaucracy reform to cut many programs that are not targeted. So, this concept was initiated by Sheikh Abdul Qadeem Zallum be considered to solve the Indonesian budgeting problems.